Financial Reporting Transparency and Earnings Management (Retracted) - Hunton, James E.; Libby, Robert; Mazza, Cheri L. (The Accounting Review, 2006)
Prior research indicates that greater transparency in reporting formats facilitates the detection of earnings management. The current study hypothesizes and demonstrates that greater transparency in comprehensive income reporting also reduces the likelihood that managers will engage in earnings management in the area of increased transparency. In our experiment, 62 financial executives and chief executive officers decide which available-for-sale security to sell from a portfolio. We manipulate the transparency of comprehensive income reporting and the relationship of projected earnings to the consensus forecast in a 2×2 between-subjects design. When projected earnings are below (above) the consensus forecast, participants sell securities that increase (decrease) earnings. However, the rarely used, more transparent format for reporting comprehensive income significantly reduces both income-increasing and income-decreasing earnings management. Participants in the less transparent setting indicate that earnings management attempts will not be obvious to readers, will improve stock prices, and have no effect on management's reputation for reporting integrity. Conversely, respondents in the more transparent condition suggest that earnings management will be obvious to readers, harmful to stock prices, and damaging to reporting reputation. Results of this study suggest that more transparent reporting requirements will reduce earnings management in the area of increased transparency or change the focus of earnings management to less visible methods.